Peran Dakwah dalam Sekolah Pranikah Masjid Salman ITB Upaya Membangun Ketahanan Keluarga - Jalaluddin Salam; Komarudin Shaleh (UNISBA Press, 2024)
Abstract. generally a sakinah marriage is the goal of many couples, but without a strong commitment, this dream is often difficult to realize. In many cases, a couple's lack of understanding of their responsibilities in marriage often ends in conflict and, in more severe situations, can end in divorce. Facing this challenge, the Salman ITB Mosque has taken a real initiative by organizing a Premarital School Program. Based on the above phenomenon, the problems are: Materials and Da'wah methods used in the Salman ITB Mosque Pre-Wedding School as well as the results of participants' understanding before and after attending the Pre-Wedding School. This research aims to analyze the materials and methods used in SPN and find out participants' understanding before and after participating in SPN Salman Mosque ITB. This type of research is qualitative, descriptive analysis approach in this research, data collection techniques through observation, interviews and documentation, comparative techniques. The results of this research are that the Salman ITB Mosque premarital school has an important role in facilitating the community, efforts to educate with aspects of solving family problems that are strengthened by spiritual aspects. Strengthened by his preaching method, everything taught at the Salman ITB Mosque Premarital School makes a real impression on the participants. So that it awakens their mindset to become an ideal family. Abstrak. Mencapai pernikahan yang sakinah merupakan tujuan banyak pasangan, namun tanpa komitmen yang kuat, impian ini sering kali sulit terwujud. Dalam banyak kasus, ketidakpahaman pasangan tentang tanggung jawab mereka dalam pernikahan sering berujung pada konflik dan, dalam situasi yang lebih parah, bisa berakhir dengan perceraian. Menghadapi tantangan ini, Masjid Salman ITB telah mengambil inisiatif nyata dengan menyelenggarakan Program Sekolah Pranikah. Berdasarkan fenomena diatas maka permasalahannya yaitu: Materi dan Metode Dakwah yang digunakan dalam Sekolah Pranikah Masjid Salman ITB serta hasil pemahaman peserta sebelum dan sesudah mengikuti Sekolah Pranikah. Penelitian ini bertujuan untuk menganalisis materi dan metode yang digunakan dalam SPN dan mengetahui pemahaman peserta sebelum dan sesudah mengikuti spn Masjid Salman ITB, jenis penelitian ini adalah kuliatatif pendekatan deskriptif dalam penelitian ini teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi., teknik analisis comparative. Hasil penelitian ini ialah sekolah pranikah Masjid Salman ITB memiliki peran penting dalam mefasilitasi masyarakat, upaya mengedukasi dengan aspek penyelesaian masalah keluarga yang diperkuat dengan aspek spiritual. Diperkuat dengan metode dakwahnya yang membuat setiap hal yang diajarkan di Sekolah Pranikah masjid Salman ITB memberikan kesan nyata pada pesertanya. Sehingga membuat mindset mereka terbangun untuk menjadi keluarga yang ideal.